KEPUTUSAN NASABAH DALAM MEMILIH PEMBIAYAAN ATAU GADAI SYARIAH - Abdul Wahab (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
When a customer needs funds and has collateral, the customer can use his collateral to carry out sharia financing or mortgage. Will customers choose sharia financing or mortgage. This causes mutually exclusive, that is if the customer chooses financing, then it does not choose sharia mortgage and vice versa. However, customers will certainly choose one of the alternatives. Therefore the purpose of this study is to find out the factors that distinguish customers in choosing financing or Islamic mortgage. The factors that are considered by customers in choosing financing or sharia pawning studied include: requirements, product variations, costs and expenses, collateral, loan value, services and location. This research is a field research with a sample of 100 people, the technique used is nonprobability sampling, namely purposive sampling, sampling techniques with certain criteria, namely customers who have made sharia financing or mortgage in the Yogyakarta region. As for the data analysis method, the compiler uses descriptive statistical methods and Correspondence Analysis. The results of this study indicate that the factor that distinguishes clients in choosing Islamic finance is the distance factor, namely the location of close Islamic finance services. While the factors that distinguish customers in choosing sharia mortgage are easy requirements